Mammalian Atg8 proteins regulate lysosome and autolysosome biogenesis through SNAREs - Gu Y; Yakubu Abudu P; Bissa B; Choi SW; Kumar S; Lazareau M; Eskelinen E-L; Johansen T; and Deretic V (Wiley-Blackwell Publishing Ltd., 2022)
Mammalian homologs of the yeast Atg8 protein (mAtg8s) are important in autophagy, but their exact mode of action remains to be defined. Recently, syntaxin 17 (Stx17), a SNARE with major roles in autophagy, was shown to bind mAtg8s. Here we broadened the analysis of potential mAtg8-SNARE interactions and identified LC3-interacting regions (LIRs) in several SNAREs. Syntaxin 16 (Stx16), and its cognate SNARE partners all have LIR motifs and bind mAtg8s. A knockout in STX16 caused defects in lysosome biogenesis whereas a double STX16 and STX17 knockout completely blocked autophagic flux and decreased mitophagy, pexophagy, xenophagy, and ribophagy. Mechanistic analyses revealed that mAtg8s and Stx16 maintained several aspects of lysosomal compartments including their functionality as platforms for active mTOR. These findings reveal a broad direct interaction of mAtg8s with SNAREs with impact on membrane remodeling in eukaryotic cells and expand the roles of mAtg8s to lysosome biogenesis.